Analisis Pengaruh Kompensasi dan Kepuasan Kerja terhadap Produktivitas Kerja Wiraniaga Suzuki Pt Restu Mahkota Karya Jakarta - Enny Ariyanto; Gazali Rahman (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2016)
AbstractThis study aims to examine the effect of compensation and job satisfaction on the labor productivity of Suzuki car salesman at PT Restu Mahkota Karya. The study sample involves 162 respondents from six personal salers from different areas and determined through saturation sampling technique. Primary data is obtained through a questionnaire. Multiple linear regression model is used to test the hypothesis of the influence of variable compensation and job satisfaction on productivity. The research proves that the variable compensation partially has no significant effect on the productivity of the sales force. However, the variable of job satisfaction has weak significant influence on the productivity of the sales force. Furthermore, simultaneous variable compensation and job satisfaction have weak significant positive effect on the productivity of the sales force of PT Restu Mahkota Karya.